THE EFFECT OF STORE ATMOSPHERE AND PRODUCT PACKAGING TOWARDS CONSUMER BUYING BEHAVIOR, AT HUSH PUPPIES STORE MANADO - Supit, Pratisia Prisilia Tifanny (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The behavior of consumer depends on a number of factors and not limited to the services that are provided in retailed stores.  Hence marketers use as many approaches as possible, in order to encourage the consumers to approach, buy and stay longer. Two of the approaches are to build up mood in their store atmosphere and the packaging of the product.  The purpose of this research is to find the effect store atmosphere and product packaging on consumer buying behavior of Hush Puppies Manado.  This research is a causal research which is based on data gathered of 53 respondents from the consumers of Hush Puppies Store Manado.  By using the multiple regression method as the analysis tool, the result shows that store atmosphere and product packaging variables have significant effect on consumer buying behavior partially and simultaneously.  As the recommendation the management of Hush Puppies store Manado should be paying attention towards store cleanliness, store design, and personnel behavior.  Furthermore, packaging products of Hush Puppies store Manado is very familiar among its consumers.  Thus, instead of changing the packaging design, Hush Puppies store management should be working on its materials and packaging color. Keywords: store atmosphere, product packaging, consumer buying behavior.